Learning about mosquitoes, diseases, and vectors: a classroom activity. (3rd July 2022) - Cocke, Teri E.; Geest, Emily A.; Shufran, Andrine A.
Abstract: Mosquitoes (Culicidae) are disease vectors, which are responsible for an estimated one million deaths per year. Female mosquitoes, which need blood for survival and reproduction, collect blood with a disease present from a host, and will transmit that disease from one host to another as it feeds on additional food sources. This continuous feeding behavior indirectly contributes to widespread disease transmission, including zoonotic diseases such as malaria, West Nile, and Zika virus from animal hosts to humans. While mosquitoes spread diseases, they also provide important ecosystem services with male mosquitoes feeding on nectar and pollinating flowering plants. Mosquitoes are also a vital food source for many organisms and are integral to many food webs. This manuscript aims to use a series of hands-on activities to introduce students to mosquitoes. Students will use worksheets and create mosquito replicas to learn about insect anatomy. The mosquito replicas will be used in an interactive disease spread and transmission activity. The students will learn how disease spread varies depending on hosts and how some mosquitoes will never carry diseases or spread them to human hosts. Students will also research and share information on common diseases spread by mosquitoes and steps to reduce and prevent disease transmission among human hosts. Overall students will gain a better understanding of mosquitoes, diseases, and insect vectors.